A really topological treatment of some aspects of Carathéodory’s theory of prime ends - Judy A. Kennedy (Revista Integración, 2023)
A homeomorphism approximation technique is applied to give (1) proofs of some theorems of C. Carathéodory, and (2) a proof of a theorem of N. Rutt. The proofs use only tools from general topology (and are new in that respect), and a generalization of a theorem of Carathéodory is obtained.